Protocol for exploring the relationship between sound localization and the representation of the body in space - Daniel Paromov; Karina Moïn-Darbari; Assan Mary Cedras; Maxime Maheu; Benoit-Antoine Bacon; François Champoux (STAR Protocols)
Summary: The influence of multisensory integration on spatial hearing has received more attention in recent years. Notably, incongruent sensory inputs can bias auditory spatial processing. Here, we present a protocol for producing an illusory shift in the localization of a sound source by inducing an unconscious shift in the representation of the body in space. We describe steps for screening participants and evaluating vestibular and hearing abilities. We then detail procedures for performing auditory localization tasks both with and without disorientation.For complete details on the use and execution of this protocol, please refer to Paromov et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.